Mitochondria and Alcohol-Associated Liver Disease: Pathogenic Role and Target for Therapy - Torres, Sandra; Hardesty, Josiah; Barrios, Monica; Garcia-Ruiz, Carmen; Fernandez-Checa, Jose C.; Singal, Ashwani K. (Seminars in Liver Disease, 2024)
Alcohol-associated liver disease (ALD) is one of the leading causes of chronic liver disease and a major cause of liver-related death. ALD is a multifactorial disease triggered by the oxidative metabolism of alcohol which leads to the activation of multiple factors that promote the progression from steatosis to more advanced stages like alcohol-associated steatohepatitis (AH) that culminate in alcohol-associated cirrhosis and hepatocellular carcinoma. Poor understanding of the complex heterogeneous pathology of ALD has limited drug development for this disease. Alterations in mitochondrial performance are considered a crucial event in paving the progression of ALD due to the crucial role of mitochondria in energy production, intermediate metabolism, calcium homeostasis, and cell fate decisions. Therefore, understanding the role of mitochondria in eliciting steatosis and progression toward AH may open the door to new opportunities for treatment. In this review, we will cover the physiological function of mitochondria, its contribution to ALD in experimental models and human disease, and explore whether targeting mitochondria may represent a game changer in the treatment of ALD.
Keywords: bioenergetics; antioxidants; oxidative stress; ROS